2016
DOI: 10.1007/s11096-016-0259-8
|View full text |Cite
|
Sign up to set email alerts
|

Influence of CYP2B6 and CYP2C19 polymorphisms on sertraline metabolism in major depression patients

Abstract: CYP2B6*6 and *9 variant alleles had a significant decreasing effect on sertraline metabolism in major depression patients which might result as variations in sertraline therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 32 publications
1
24
0
Order By: Relevance
“…To stratify the extent of drug‐gene interactions, a comparison of current and previous medications aligned with metabolic enzyme pathway can be seen in Table . It was observed that citalopram and sertraline are metabolized by CYP2C19 (OMIM#124020) (Uckun et al, ; Yuce‐Artun et al, ), and risperidone, aripiprazole, dextroamphetamine, dexamphetamine, and catapres are metabolized by CYP2D6 (OMIM#124030) (Claessens et al, ; Dodsworth et al, ; Lisbeth et al, ; Miranda‐G. et al, ; Teh & Bertilsson, ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To stratify the extent of drug‐gene interactions, a comparison of current and previous medications aligned with metabolic enzyme pathway can be seen in Table . It was observed that citalopram and sertraline are metabolized by CYP2C19 (OMIM#124020) (Uckun et al, ; Yuce‐Artun et al, ), and risperidone, aripiprazole, dextroamphetamine, dexamphetamine, and catapres are metabolized by CYP2D6 (OMIM#124030) (Claessens et al, ; Dodsworth et al, ; Lisbeth et al, ; Miranda‐G. et al, ; Teh & Bertilsson, ).…”
Section: Resultsmentioning
confidence: 99%
“…To stratify the extent of drug-gene interactions, a comparison of current and previous medications aligned with metabolic enzyme pathway can be seen in Table 3. It was observed that citalopram and sertraline are metabolized by CYP2C19 (OMIM#124020) (Uckun et al, 2015;Yuce-Artun et al, 2016), and risperidone, aripiprazole, dextroamphetamine, dexamphetamine, and catapres are metabolized by CYP2D6 (OMIM#124030) (Claessens et al, 2010;Dodsworth et al, 2018;Lisbeth et al, 2016;Miranda-G. et al, 2007;Teh & Bertilsson, 2012). The RightMed comprehensive test reported Patient 1 as an intermediate phenotype for each of these genes, including decreased metabolic activity, stating that "drugs converted to active metabolites may have reduced efficacy.…”
Section: Pharmacogenomics Testing Utilized To Identify Possible Drumentioning
confidence: 99%
“…CYP2B6 has frequent polymorphisms that induce a dynamic range of activity, leading directly to hepatotoxicity and mortality during administration of common drugs [4042]. New suspension culture methods that introduce physiological levels of shear can now maintain expression of CYP2B6 in vitro [5, 33].…”
Section: Discussionmentioning
confidence: 99%
“…CYP2B6 has also been reported to be expressed in human brain tissue, unlike CYP2A6, and it has therefore been proposed that genetic variation affecting the CYP2B6 enzyme might play a significant role in nicotine‐related phenotypes . CYP2B6 is highly polymorphic, and common haplotypes, especially CYP2B6*6 and *9 , containing 516G>T (Q172H, minor allele frequency 26% in European Americans, 37% in African Americans (http://evs.gs.washington.edu/EVS/)) are associated with clinically significantly altered pharmacokinetics for different substrates, relative to the reference allele . Because the effects of CYP2B6 polymorphisms on CYP2B6 activity is substrate‐specific, activities of different CYP2B6 isoforms cannot be assumed for untested substrates, such as nicotine.…”
Section: Introductionmentioning
confidence: 99%
“…13 CYP2B6 is highly polymorphic, and common haplotypes, especially CYP2B6*6 and *9, containing 516G>T (Q172H, minor allele frequency 26% in European Americans, 37% in African Americans (http://evs.gs.washing ton.edu/EVS/)) are associated with clinically significantly altered pharmacokinetics for different substrates, relative to the reference allele. [14][15][16][17][18][19] Because the effects of CYP2B6 polymorphisms on CYP2B6 activity is substrate-specific, activities of different CYP2B6 isoforms cannot be assumed for untested substrates, such as nicotine. Therefore, we have expressed polymorphic CYP2B6 enzymes and measured their nicotine metabolism activity in vitro.…”
mentioning
confidence: 99%